Efficacy and safety of two dosages of canrenone as add‐on therapy in hypertensive patients taking ace‐inhibitors or angiotensin II receptor blockers and hydrochlorothiazide at maximum dosage in a randomized clinical trial: The ESCAPE‐IT trial. Issue 1 (February 2017) - Derosa, Giuseppe; Maffioli, Pamela; D'Avino, Maria; Sala, Carla; Mugellini, Amedeo; Vulpis, Vito; Felis, Salvatore; Guasti, Luigina; Sarzani, Riccardo; Bestetti, Alessandro; Vanasia, Massimo; Gaudio, Giovanni; et al.
Summary: Aim: To evaluate the effects of canrenone as add‐on therapy in patients already treated with angiotensin‐converting enzyme inhibitors (ACE‐I) or angiotensin II receptor blockers (ARBs) and hydrochlorothiazide at the maximum dosage (25 mg/d). Method: In this randomized, open‐label, controlled trial, we enrolled 175 Caucasian patients with essential hypertension not well controlled by concomitant ACE‐I or ARBs and hydrochlorothiazide. At baseline, 87 patients (57 males and 30 females) were randomized to add canrenone 50 mg, and 88 (56 males and 32 females) patients to canrenone 100 mg, once a day, for 3 months. At baseline and after 3 months, we evaluated blood pressure (BP), pulse pressure (PP), heart rate (HR), fasting plasma glucose (FPG), homeostasis model assessment insulin (HOMA Index), lipid profile, electrolytes, uric acid, estimated glomerular filtration rate (eGFR), plasma urea, aldosterone, B‐type natriuretic peptide (BNP), and galectin‐3. Results: Blood pressure decreased with both dosages of canrenone, with a better effect with canrenone 100 mg (−20.26 vs −23.68 mm Hg for SBP, and −10.58 vs −12.38 mm Hg for DBP), without a clinically relevant increase in potassium levels. We did not observe any differences regarding FPG or HOMA Index, nor of lipid profile, with the exception of triglycerides, which increased compared to baseline with canrenone 50 mg (+0.25 vs +0.34 mEq/L). Creatinine slightly increased with canrenone 100 mg (+0.02 vs +0.05 mg/dL), although no variations of eGFR were observed in neither groups. There was an increase in aldosterone levels with canrenone 50 mg. No changes in BNP or galectin‐3 were recorded. Conclusion: Both canrenone dosages gave a decrease in blood pressure, with a better effect with the higher dose, with only a slight increase in potassium and creatinine levels, which were not clinically relevant. Clinical Trials Registration Eudract number: 2010‐023606‐13; ClinicalTrials.gov NCT02687178.